Solid wall insulation of the Victorian house stock in England: A whole life carbon perspective. (15th March 2021) - Li, Xinyi; Densley Tingley, Danielle
Abstract: Solid walls are a common feature of the pre-1919 Victorian housing stock in England, however their construction results in considerable heat loss, and thus large heating requirements. Solid wall insulation of these walls would improve energy efficiency, and in turn should reduce greenhouse gas emissions. However, the additional insulation needed comes with an embodied carbon cost. Current studies about whole life performance of solid wall insulation focus on a single building or building type only, without considering the diversity of building types in the pre-1919 Victorian house stock. This study fills this gap by investigating the whole life carbon performance of eight current market available insulation materials. The insulation materials studied include vacuuminsulated panels (VIPs), aerogel, phenolic foam, polyurethane (PUR), polyisocyanurate (PIR), expanded polystyrene (EPS), glass wool and wood fibre. The results show that solid wall insulation reduces whole life carbon emissions up to 1654 kgCO2 e per m 2, with the carbon payback time of all eight insulation materials being less than 23 years in the worst case scenario, and less than one year in the best case scenario. Both are considerably shorter than the service life of the insulation materials. More actions should be taken to promote the installation of solid wall insulation in the pre-1919 Victorian house stock as this work shows that the accumulated carbon reduction potential reached 268 MtCO2 e from 2021 to 2050. Highlights: Archetype approach used to considering the variation of Victorian house stock. Whole life carbon analysis including both embodied and operational carbon emissions. Solid wall insulation led to whole life carbon reduction and short payback time.